Pengaruh Augmented Reality (Virtual Try-On) terhadap Purchase Intention Produk Kosmetik melalui Customer Satisfaction - Natasya Zulfia Abriani; Muhammad Fajar Wahyudi Rahman (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2026)
This study aims to examine and analyze the effect of augmented reality (virtual try-on) on purchase intention through customer satisfaction for Maybelline cosmetic products on the Shopee marketplace. The study applied an explanatory quantitative approach, and data were collected using a Likert-scale questionnaire. The sample was selected through non-probability sampling with a purposive sampling method involving 212 female respondents who had seen, known, or purchased Maybelline cosmetic products on Shopee and had used the Shopee BeautyCam feature. The data were analyzed using Structural Equation Modelling-Partial Least Square with Smart-PLS 3.0. The findings show that augmented reality has a positive effect on customer satisfaction with a coefficient of 0.899, t-statistic of 36.597, and p-value of 0.000. Augmented reality also has a positive effect on purchase intention with a coefficient of 0.777, t-statistic of 14.899, and p-value of 0.000. Customer satisfaction positively affects purchase intention with a coefficient of 0.193, t-statistic of 3.671, and p-value of 0.000. Furthermore, customer satisfaction mediates the effect of augmented reality on purchase intention with a coefficient of 0.173, t-statistic of 3.702, and p-value of 0.000. These results indicate that an interactive, realistic, and novel virtual try-on experience can increase customer satisfaction and strengthen purchase intention toward Maybelline cosmetic products on Shopee.